Anisaxins, helical antimicrobial peptides from marine parasites, kill resistant bacteria by lipid extraction and membrane disruption. (1st July 2022) - Rončević, Tomislav; Gerdol, Marco; Mardirossian, Mario; Maleš, Matko; Cvjetan, Svjetlana; Benincasa, Monica; Maravić, Ana; Gajski, Goran; Krce, Lucija; Aviani, Ivica; Hrabar, Jerko; Trumbić, Željka; et al.
Abstract: An infecting and propagating parasite relies on its innate defense system to evade the host's immune response and to survive challenges from commensal bacteria. More so for the nematode Anisakis, a marine parasite that during its life cycle encounters both vertebrate and invertebrate hosts and their highly diverse microbiotas. Although much is still unknown about how the nematode mitigates the effects of these microbiota, its antimicrobial peptides likely play an important role in its survival. We identified anisaxins, the first cecropin-like helical antimicrobial peptides originating from a marine parasite, by mining available genomic and transcriptomic data for Anisakis spp. These peptides are potent bactericidal agents in vitro, selectively active against Gram-negative bacteria, including multi-drug resistant strains, at sub-micromolar concentrations. Their interaction with bacterial membranes was confirmed by solid state NMR (ssNMR) and is highly dependent on the peptide concentration as well as peptide to lipid ratio, as evidenced by molecular dynamics (MD) simulations. MD results indicated that an initial step in the membranolytic mode of action involves membrane bulging and lipid extraction; a novel mechanism which may underline the peptides' potency. Subsequent steps include membrane permeabilization leading to leakage of molecules and eventually cell death, but without visible macroscopic damage, as shown by atomic force microscopy and flow cytometry. This membranolytic antibacterial activity does not translate to cytotoxicity towards human peripheral blood mononuclear cells (HPBMCs), which was minimal at well above bactericidal concentrations, making anisaxins promising candidates for further drug development. Statement of significance: Witnessing the rapid spread of antibiotic resistance resulting in millions of infected and dozens of thousands dying worldwide every year, we identified anisaxins, antimicrobial peptides (AMPs) from marine parasites, Anisakis spp., with potent bactericidal activity and selectivity towards multi-drug resistant Gram-negative bacteria. Anisaxins are membrane-active peptides, whose activity, very sensitive to local peptide concentrations, involves membrane bulging and lipid extraction, leading to membrane permeabilization and bacterial cell death. At the same time, their toxicity towards host cells is negligible, which is often not the case for membrane-active AMPs, therefore making them suitable drug candidates. Membrane bulging and lipid extraction are novel concepts that broaden our understanding of peptide interactions with bacterial functional structures, essential for future design of such biomaterials. Graphical abstract: Image, graphical abstract